The Fate of Polish Immigrants in Winnipeg ? a Contribution (To) Learn from Own Biography - Januszewska, Edyta (INSTED: Interdisciplinary Studies in Education & Society, 2014)
This article raises the issue of immigration to Canada of Poles who came to that country in years 1945?1989. The text consists of three parts. The first relates to the theoretical concept of ?trajectory? and ?biographical learning?, which approximates the various positions and approaches to the concept of learning from its own experience. In the second part I focus on the beginnings of Polish immigration to Canada, the present wave of Polish migration and I briefly characterize the situation of Polish pioneers and veterans of World War II in the province of Manitoba. The third section attempts to describe the difficulties and (self-) reflection in the narrative on own experiences and biographical learning in the context of own biography subjects.